Co‐occurrence of autism, childhood psychosis, and intellectual disability associated with a de novo 3q29 microdeletion12. Issue 4 (26th February 2013) - Sagar, Angela; Bishop, Jeffrey R.; Tessman, D. Clare; Guter, Steve; Martin, Christa L.; Cook, Edwin H.
Abstract Some copy number variants (CNVs) are strongly implicated in both schizophrenia and autism spectrum disorders (ASDs). Childhood‐onset schizophrenia (COS) occurs rarely with 0.1–1% of all schizophrenia diagnoses manifesting before age 10. 3q29 deletions are associated with both autism and schizophrenia, and are rare—the frequency of the deletion estimated to be 1 in 1, 750 in developmental disorders. Only one patient with a 3q29 deletion was identified out of the first 1, 174 families with ASDs included in the Simons Simplex Collection (SSC). We report on detailed clinical findings for this patient with a de novo 3q29 deletion who, as a young child, developed a very rare overlap of symptoms of both autism and early onset psychosis. His ASD was first diagnosed at the age of 4 years and his psychotic symptoms began at 5 years old. This is only the second case reported thus far of this rare event of co‐occurring autism and very early onset psychosis in a child with a 3q29 deletion. It is also the earliest case of a child with autism developing comorbid psychosis—manifesting by the age of 5 years. © 2013 Wiley Periodicals, Inc.